Numerical Simulation to See the Performance of Groynes and Breakwaters as Shore-Protection Structures at Ketaping Beach, Padang Pariaman - Hariatama, Adean; Mera, Mas (Jurnal Talenta Sipil, 2025)
This research is about numerical simulation to find out the performance of groynes and breakwaters as shore-protection structures in Ketaping Beach, Padang Pariaman (West Sumatra-Indonesia) using an existing software. The effectiveness of a shore-protection structure can be seen from the height and area of the bathymetry formed by the structure. The direction of incoming waves in the deep sea for all simulations is based on the dominant wave direction, namely from the west. The tide conditions were taken during Eid al-Fitr 1442 H because at that time there was an extreme tide. Based on the consideration of running time on the computer, the selected simulation time span is only 5 days (22 to 26 May 2020). The simulation for 5 days shows that the performance of breakwaters is more effective than groynes in protecting Ketaping Beach from abrasion. Sedimentation formed behind the breakwater as high as 20 to 80 cm above the initial elevation. Meanwhile, groyne performance is only effective at holding sediment along the groyne as high as 10 cm to 30 cm above the initial elevation.